2008
DOI: 10.1007/s10157-008-0060-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress in the kidney

Abstract: Endoplasmic reticulum (ER) stress is involved in a wide range of pathological circumstances including neurodegenerative disorders, diabetes mellitus, ischemic injury, cancers, atherosclerosis, inflammation, infection, toxicity of chemicals and metals, and psychotic diseases. ER stress is also involved in some physiological events including development of particular cell types. A number of pathophysiological triggers cause accumulation of unfolded proteins in the ER, i.e., ER stress. In response to accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 69 publications
1
54
0
4
Order By: Relevance
“…Fang et al reported that ERS appeared to play an important part in albuminuriaprovoked inflammasome activation and elimination of ERS via tauroursodeoxycholic acid (TUDCA), which might represent a novel avenue for attenuating kidney epithelial cell damage caused by albuminuria (34). The UPR is a homeostatic response that allows the cells to cope with stressful conditions associated with increased misfolded or unfolded protein loads; failure of this mechanism is referred to as the ERS response (9).The ERS response has been found to play a key role in a growing number of pathological conditions such as DN (10,34,35), and the ERS response is considered to be a cause of chronic inflammation (36). The current results verified the hypothesis that DN is related to ERS via dysregulated expression of GRP78, p-PERK, p-eIF2α, and CHOP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fang et al reported that ERS appeared to play an important part in albuminuriaprovoked inflammasome activation and elimination of ERS via tauroursodeoxycholic acid (TUDCA), which might represent a novel avenue for attenuating kidney epithelial cell damage caused by albuminuria (34). The UPR is a homeostatic response that allows the cells to cope with stressful conditions associated with increased misfolded or unfolded protein loads; failure of this mechanism is referred to as the ERS response (9).The ERS response has been found to play a key role in a growing number of pathological conditions such as DN (10,34,35), and the ERS response is considered to be a cause of chronic inflammation (36). The current results verified the hypothesis that DN is related to ERS via dysregulated expression of GRP78, p-PERK, p-eIF2α, and CHOP.…”
Section: Discussionmentioning
confidence: 99%
“…GRP78 is a marker of ERS and has been implicated in the pathogenesis of diabetic complications (9). GRP78 was noted in the glomerulus and tubulointerstitium.…”
Section: Tgp Inhibited the Expression Of Grp78 In The Kidneys Of Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the key role of the ER in protein synthesis and proper folding, cellular stresses such as hypoxia, glucose depletion, and oxidative damage may lead to ER dysfunction and the accumulation of unfolded/misfolded proteins, which are categorized as ER stress (41). In response to these linked events, UPR as an adaptive or proapoptotic response will be activated (5,6). Herein, we have focused on transcription levels of the UPR markers GRP78 and XBP1 after induction of I/R in rat kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…The endoplasmic reticulum (ER), as an important intracellular organelle responsible for protein synthesis, folding, trafficking, and modification, is susceptible to many stresses such as ischemia, oxidative stress, nutrient depletion, toxins, and hypoxia. These endogenous or exogenous disturbances can result in unfolded/misfolded protein accumulation and the subsequent activation of an unfolded protein response (UPR) (4)(5)(6)(7). Glucose-regulated protein (GRP) 78 (also known as BiP: immunoglobulin heavy-chain-binding protein) is a central modulator of the UPR that normally binds to and prevents aggregation of unfolded/misfolded proteins in the ER (6,8).…”
Section: Introductionmentioning
confidence: 99%